Connecting with Generation Z: Approaches in Nursing Education - Chicca, Jennifer; Shellenbarger, Teresa (Teaching and learning in nursing, 2018)
Generation Z, a unique and truly digital native generation, is now entering college and the workplace. This article identifies generational influences and distinctive characteristics of this group, which may challenge nurse educators and require changes in teaching–learning design strategies and approaches. Specific educational suggestions and ways to support members of Generation Z in higher education and the workplace are offered. •Gen Z students, born between the mid-1990s and 2012, are entering higher education.•Gen Z brings distinctive generational attributes that will impact education.•Teaching–learning design strategies and approaches must be offered to support Gen Z.•Faculty must consider classroom, clinical, and other changes to help Gen Z students.